Wrinkle-resistant cotton fiber composite fabric and preparation method thereof

By combining cotton fibers, porous polyester fibers and chitosan fibers and plasma treatment of cotton fibers, the problem of cotton fibers being easily wrinkled is solved, and the fabric is highly wrinkle-resistant, soft and breathable.

CN119777168APending Publication Date: 2025-04-08WUJIANG XINGYE TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411769138.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Cotton fibers are prone to wrinkles. Existing anti-wrinkle methods will affect the softness and hygroscopicity of the fibers, and may retain chemical additives that are not good for health.

Method used

The composite fabric of 60-70% cotton fiber, 20-25% porous polyester fiber and 5-15% chitosan fiber is used. The cotton fiber is plasma treated and combined with porous polyester fiber and chitosan fiber to increase the binding force and wrinkle resistance of the fiber.

Benefits of technology

It maintains the softness and hygroscopicity of cotton fibers, while significantly improving wrinkle resistance, enhancing the breathability and comfort of the fabric, making it suitable for long-term wear.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of cotton fabrics, and specifically discloses an anti-wrinkle cotton fiber composite fabric and a preparation method thereof. The anti-wrinkle cotton fiber composite fabric comprises 60-70% cotton fiber, 20-25% porous polyester fiber, and 5-15% chitosan fiber, wherein the cotton fiber is treated with plasma; and the preparation method thereof comprises: blending cotton fiber, porous polyester fiber, and chitosan fiber to obtain composite yarn, and then weaving the composite yarn to obtain the anti-wrinkle cotton fiber composite fabric. The anti-wrinkle cotton fiber composite fabric of the present application has the advantages of maintaining soft moisture absorption and breathability while having good anti-wrinkle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cotton fabrics, and more specifically, to an anti-wrinkle cotton fiber composite fabric and a preparation method thereof. Background Art

[0002] Cotton fiber is the most common natural fiber in daily life and is widely used in various textiles. For example, T-shirts, bed sheets, towels, etc. are mostly made of cotton fiber. Cotton fiber is deeply loved by everyone because of its softness, good moisture absorption and strong breathability.

[0003] The main component of cotton fiber is cellulose. There are many hydrogen bonds in the cellulose molecular structure. These hydrogen bonds connect the cellulose molecules, giving cotton fiber good strength and hygroscopicity. But at the same time, it also makes cotton fiber easy to deform with changes in the environment, causing wrinkles in the fabric, thus affecting the appearance and wearing comfort.

[0004] In order to deal with the problem of cotton fibers being prone to wrinkling, the most common method is to use resin finishing or chemical additives, which can react with cellulose molecules to form a more stable structure, preventing cellulose from deforming after being subjected to external forces, thereby achieving an anti-wrinkle effect. Although this method does improve wrinkle resistance, it also brings some problems. After cotton cloth is treated with resin, it will feel harder and no longer as soft and comfortable as before. Chemical treatment may also affect the hygroscopicity of cotton fibers, making them less breathable and sweat-absorbent when worn. Some chemical additives may remain in the fabric during the processing process, and long-term contact with the skin may have adverse effects on health. Summary of the invention

[0005] In order to make cotton fiber fabrics maintain softness, moisture absorption and breathability while having good anti-wrinkle performance, the present application provides an anti-wrinkle cotton fiber composite fabric and a preparation method thereof.

[0006] The present application provides an anti-wrinkle cotton fiber composite fabric adopts the following technical solution: A wrinkle-resistant cotton fiber composite fabric comprises 60-70% cotton fiber, 20-25% porous polyester fiber and 5-15% chitosan fiber, wherein the cotton fiber is treated with plasma.

[0007] By adopting the above technical scheme, cotton fibers are treated with plasma, and plasma can make them more active through high-energy particles hitting the fiber surface, thereby enhancing the fiber's ability to bind with other materials. The cotton fibers treated in this way not only maintain their original softness and hygroscopicity, but also improve their surface structure, which helps to improve the wrinkle resistance of the fabric. 20-25% porous polyester fibers are added to the fabric, and the porous structure provides better air permeability for the fibers, while increasing the wrinkle resistance of the fibers while maintaining lightness. Porous polyester fibers can also increase air circulation between fibers, further improving the wearing comfort of the fabric. Chitosan fibers have antibacterial and antistatic properties. Its combination with cotton fibers and porous polyester fibers helps to improve the functionality of the fabric, while enhancing the flexibility and wrinkle resistance of the fabric. The addition of chitosan can also improve the hygroscopicity of the fabric, allowing the fabric to maintain a comfortable wearing experience in a humid environment. Through the combination of the above materials, this fabric not only maintains the original hygroscopicity, breathability and softness of cotton fabrics, but also significantly improves the wrinkle resistance.

[0008] Optionally, the specific steps of plasma treating cotton fibers are: The cotton fibers were laid flat and treated for 30-60 seconds in a high-frequency electric field with a power of 120-180 W in a 300-500 Pa nitrogen environment.

[0009] By adopting the above technical scheme, the surface of cotton fiber after plasma treatment becomes rougher and more active, which enhances the interaction with porous polyester fiber and chitosan fiber, making the bonding between fibers inside the fabric tighter. Under the action of external force, the displacement between fibers is reduced, thereby enhancing the wrinkle resistance of the fabric and reducing the deformation and wrinkles of the fibers. Although plasma treatment changes the fiber surface, it has little effect on the softness and air permeability of the fiber. The plasma treatment time is controlled at 30-60 seconds, ensuring that the fiber treatment depth is moderate, thereby retaining the softness and air permeability of the cotton fiber itself while improving the surface activity. Nitrogen plasma can increase the number of hydrophilic groups on the fiber surface, thereby improving the hygroscopicity of cotton fibers. This modification helps the fabric to maintain a comfortable wearing feel under humid or high humidity conditions, especially when used in conjunction with chitosan fibers. This effect is more significant.

[0010] Optionally, a polyurethane anti-wrinkle agent is also included, and the amount of the polyurethane anti-wrinkle agent is 2-4% of the total mass of the fabric.

[0011] Optionally, the components of the polyurethane anti-wrinkle auxiliary agent include, by weight percentage, 40-50% aqueous polyurethane dispersion, 3-5% citric acid, 5-10% sodium alginate, 8-12% vegetable oil-based silicone, 1-3% cellulose nanocrystals and 0.5-2% soybean lecithin.

[0012] By adopting the above technical scheme, waterborne polyurethane forms a flexible mesh structure between fabric fibers, giving the fabric excellent elastic recovery, so that it can quickly return to its original shape when compressed by external force, reducing the generation of wrinkles. Citric acid, as a cross-linking agent in the additive, can react with the hydroxyl groups in the cellulose fibers to form a chemical cross-linking structure. This reaction effectively enhances the bonding force between the fibers and reduces the possibility of fiber deformation in the fabric, thereby improving the anti-wrinkle performance. Sodium alginate has good moisture retention and film-forming properties. It forms a protective film on the surface of the fabric, which helps to maintain the moisture balance between the fibers and improve the durability and comfort of the fabric. The addition of plant oil-based siloxane makes the surface of the fabric smoother, reduces the friction between the fibers, and improves the wrinkle resistance and water resistance. The hydrophobicity of siloxane can also prevent the fabric from absorbing too much water in a humid environment, further reducing the generation of wrinkles. Cellulose nanocrystals can enhance the mechanical stability between fibers, reduce the displacement of fibers, and thus improve the anti-wrinkle effect of the fabric. In addition, the nanocrystalline structure helps to maintain the morphological stability of the fabric, so that the fabric can remain flat after long-term use. Soy lecithin, as a natural surfactant, can improve the uniform distribution of additives on the fabric and enhance the synergy between the ingredients. The addition of lecithin makes the fabric softer and more comfortable to wear.

[0013] Optionally, the chitosan fiber is a shape memory polymer composite chitosan fiber.

[0014] Optionally, the preparation method of the shape memory polymer composite chitosan fiber is: The photosensitized PCL is dissolved in tetrahydrofuran to prepare a polymer solution with a mass fraction of 8%-15%, and chitosan is dissolved in a 3% mass concentration acetic acid solution to form a uniform solution with a mass concentration of chitosan of 10-15%; The photosensitized PCL solution and the chitosan solution were mixed in a mass ratio of (7-8):(4-5), and shape memory polymer composite chitosan fibers were prepared by electrospinning.

[0015] By adopting the above technical solution and introducing photosensitized PCL, the fiber has shape memory properties. PCL (polycaprolactone) itself has good plasticity and reconfigurability, while photosensitized PCL further enhances its responsiveness to light and ultraviolet rays, and has a certain reversibility, which is crucial for anti-wrinkle, repair and other needs. In composite materials, chitosan not only provides biocompatibility, but also improves the hydrophilicity of the fiber and enhances its interaction with water, thereby improving the hygroscopicity and comfort of the fiber. After combining with PCL, the composite fiber retains the excellent properties of chitosan and gives it more stable physical properties. Fibers prepared by electrospinning technology usually have a higher specific surface area and mechanical strength. The composite chitosan fiber prepared by this method has a more uniform and compact structure due to electrospinning, which improves the tensile strength and wear resistance of the fiber.

[0016] In a second aspect, the present application provides a method for preparing a wrinkle-resistant cotton fiber composite fabric, using the following technical solution: A method for preparing a wrinkle-resistant cotton fiber composite fabric comprises the steps of blending cotton fiber, porous polyester fiber and chitosan fiber to obtain composite yarn, and then weaving the composite yarn to obtain the wrinkle-resistant cotton fiber composite fabric.

[0017] Optionally, the surface of the wrinkle-resistant cotton fiber composite fabric obtained by weaving is evenly sprayed with a polyurethane anti-wrinkle agent and then dried.

[0018] By adopting the above technical solution, cotton fibers are blended with porous polyester fibers and chitosan fibers, which not only improves the wrinkle resistance of cotton fibers, but also effectively reduces the crease generation of fabrics by increasing the interaction between fibers and the compactness of the fiber structure. At the same time, spraying polyurethane anti-wrinkle additives further enhances the anti-wrinkle effect of the fabric, allowing it to maintain a smooth appearance after long-term use and washing. By blending porous polyester fibers, the fabric obtains higher mechanical strength and tear resistance. Polyester fibers have higher tensile strength and wear resistance, which can improve the durability of the entire fabric. In addition, the addition of chitosan fibers also increases the elasticity and flexibility of the fabric, making it more comfortable and less prone to damage during daily wear.

[0019] In summary, this application has the following beneficial effects: 1. Since the present application is composed of 60-70% cotton fiber, 20-25% porous polyester fiber and 5-15% chitosan fiber, the cotton fiber is treated with plasma to make its surface more active, thereby enhancing the bonding strength with other fibers while retaining softness and hygroscopicity. The porous polyester fiber gives the fabric good air permeability and lightness, and enhances the anti-wrinkle effect. The chitosan fiber provides antibacterial, antistatic and hygroscopic properties, so that the fabric remains comfortable in a humid environment. The overall fabric not only has excellent moisture absorption and breathability, but also significantly improves wrinkle resistance and flexibility, making it suitable for long-term wear.

[0020] 2. In this application, polyurethane anti-wrinkle additives are preferably used, including water-based polyurethane dispersion, citric acid, sodium alginate, vegetable oil-based silicone, cellulose nanocrystals and soybean lecithin. Water-based polyurethane forms a flexible mesh structure between fibers, enhances elastic recovery and reduces wrinkles. Citric acid acts as a cross-linking agent to improve fiber bonding, and sodium alginate forms a protective film to improve fabric durability and comfort. Vegetable oil-based silicone makes the fabric smooth and waterproof, cellulose nanocrystals enhance mechanical stability, and soybean lecithin improves the distribution and softness of the additives, which significantly improves the overall anti-wrinkle effect and wearing comfort.

[0021] 3. Shape memory polymer composite chitosan fiber is preferably used in this application, and the preparation method includes an electrospinning process using photosensitized PCL and chitosan. Photosensitized PCL gives the fiber shape memory properties, enhances its responsiveness to light and ultraviolet rays, provides reversibility, and helps anti-wrinkle and self-repair. Chitosan not only enhances the biocompatibility and hygroscopicity of the fiber, but also improves comfort. Through electrospinning technology, the fiber has a higher specific surface area and mechanical strength, which overall improves the tensile strength and wear resistance of the fiber. DETAILED DESCRIPTION

[0022] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0023] Preparation example of plasma treated cotton fiber Preparation Example 1 The specific steps of plasma treatment of cotton fibers are: The cotton fibers to be treated are evenly spread on the workbench of the treatment device to ensure that the fiber surface is fully exposed, avoiding overlapping or stacking, and ensuring that the plasma can evenly contact the fiber surface.

[0024] The pressure in the cavity of the processing device is adjusted to 400Pa through the equipment control system, and nitrogen is filled into the cavity to ensure that the entire processing process is carried out in a nitrogen atmosphere.

[0025] Adjust the power of the plasma treatment device to 160W and ensure that the high-frequency electric field it generates can work stably. Turn on the plasma device, and the high-energy particles in the plasma will interact with the surface of the cotton fiber.

[0026] After the treatment time reaches 45 seconds, the equipment is turned off, the nitrogen is exhausted, and the treated cotton fibers are taken out.

[0027] Preparation example of shape memory polymer composite chitosan fiber Preparation Example 2 A method for preparing shape memory polymer composite chitosan fiber: 50 kg of polycaprolactone (PCL) was dissolved in 200 kg of anhydrous dichloromethane (DCM), and the solution was stirred until the PCL was completely dissolved.

[0028] In another container, 0.1 kg of cinnamic acid, 2 kg of dicyclohexylcarbodiimide (DCC) and 0.1 kg of 4-dimethylaminopyridine (DMAP) were dissolved in 20 kg of anhydrous dichloromethane, and the mixture was stirred for 2 hours.

[0029] The stirred cinnamic acid mixture was added dropwise to the dissolved PCL solution, the mixture was stirred continuously, and the temperature was maintained at 50°C for 24 hours. During this process, cinnamic acid will react with PCL molecules to generate photosensitized PCL.

[0030] After the reaction is completed, the by-products in the reaction system are filtered out using a filtering device to obtain a pure photosensitized PCL solution, and methanol is gradually added to the photosensitized PCL solution to precipitate the target product. Subsequently, the precipitate is washed with deionized water to remove residual solvents and impurities, and the washed precipitate is vacuum dried to ensure that the water and residual solvent therein are completely evaporated to obtain dry photosensitized PCL.

[0031] The photosensitized PCL was dissolved in tetrahydrofuran (THF) to prepare a polymer solution with a mass fraction of 12%. Chitosan was dissolved in an acetic acid solution with a mass concentration of 2%-3%, and stirred until completely dissolved to form a uniform chitosan solution with a mass concentration of 13%.

[0032] The photosensitized PCL solution and the chitosan solution were mixed in a mass ratio of 7-8:4-5, the excess solvent was removed by a rotary evaporator, the solution viscosity was adjusted to 3000 mPa·s, the mixed solution was injected into the syringe of the electrospinning device, the voltage was set at 15 kV, the flow rate was adjusted to 0.8 mL / h, the receiving distance was set to 15 cm, and the equipment was started for spinning to form shape memory polymer composite chitosan fibers.

[0033] Preparation Example 3 A preparation method of shape memory polymer composite chitosan fiber: The difference from Preparation Example 2 is that the photosensitized PCL is dissolved in tetrahydrofuran (THF) to prepare a polymer solution with a mass fraction of 8%. Chitosan is dissolved in an acetic acid solution with a mass concentration of 3%, and stirred until completely dissolved to form a uniform chitosan solution with a mass concentration of 15%.

[0034] Preparation Example 4 A method for preparing shape memory polymer composite chitosan fiber: The difference from Preparation Example 2 is that the photosensitized PCL is dissolved in tetrahydrofuran (THF) to prepare a polymer solution with a mass fraction of 15%. Chitosan is dissolved in an acetic acid solution with a mass concentration of 3%, and stirred until completely dissolved to form a uniform chitosan solution with a mass concentration of 10%. Preparation Example 5 A method for preparing shape memory polymer composite chitosan fiber: The method is different from Preparation Example 2 in that the photosensitized PCL solution and the chitosan solution are mixed in a mass ratio of 8:4.

[0035] Preparation Example 6 A method for preparing shape memory polymer composite chitosan fiber: The method is different from Preparation Example 2 in that the photosensitized PCL solution and the chitosan solution are mixed in a mass ratio of 7:5.

[0036] Preparation Example 7 A method for preparing shape memory polymer composite chitosan fiber: The method is different from Preparation Example 2 in that the photosensitized PCL solution and the chitosan solution are mixed in a mass ratio of 6:6.

[0037] Preparation Example 8 A method for preparing shape memory polymer composite chitosan fiber: The method is different from Preparation Example 2 in that the photosensitized PCL solution and the chitosan solution are mixed in a mass ratio of 9:3. Example

[0038] Example 1 A method for preparing a wrinkle-resistant cotton fiber composite fabric: Cotton fibers with a length of 30-35 mm and a fineness of 1.8 dtex were prepared, and the cotton fibers were subjected to plasma treatment according to the method of Preparation Example 1; Prepare porous polyester fibers with a length of 30-40 mm, a fineness of 1.2 dtex, a pore size between 1-5 μm, and a porosity of 40%; Chitosan fibers with a length of 40-50 mm, a fineness of 1.0 dtex, and a chitosan content of 95% were prepared.

[0039] 6.5 kg of cotton fiber, 2.5 kg of porous polyester fiber and 1 kg of chitosan fiber were uniformly mixed using an opener and a mixer, and the mixed fibers were spun into composite yarn using a blending machine, and the yarn count of the yarn was 30s.

[0040] The spun composite yarn is plain woven on a loom with a weaving density of 120*90 yarns / 10cm.

[0041] After weaving, the fabric was heat-set at 160° C. for 2 minutes to obtain a wrinkle-resistant cotton fiber composite fabric.

[0042] Example 2 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 1 is that 6 kg of cotton fiber, 2.5 kg of porous polyester fiber and 1.5 kg of chitosan fiber are uniformly mixed, and the mixed fiber is spun into composite yarn using a blending machine.

[0043] Example 3 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 1 is that 7 kg of cotton fiber, 2.5 kg of porous polyester fiber and 0.5 kg of chitosan fiber are uniformly mixed, and the mixed fiber is spun into composite yarn using a blending machine.

[0044] Example 4 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 1 is that the chitosan fiber uses shape memory polymer composite chitosan fiber, and the shape memory polymer composite chitosan fiber is prepared by Preparation Example 2.

[0045] Example 5 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 3.

[0046] Example 6 A method for preparing an anti-wrinkle cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 4.

[0047] Example 7 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 5.

[0048] Example 8 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 6.

[0049] Example 9 A method for preparing a wrinkle-resistant cotton fiber composite fabric: Cotton fibers with a length of 30-35 mm and a fineness of 1.8 dtex were prepared, and the cotton fibers were subjected to plasma treatment according to the method of Preparation Example 1; Prepare porous polyester fibers with a length of 30-40 mm, a fineness of 1.2 dtex, a pore size between 1-5 μm, and a porosity of 40%; Prepare chitosan fibers with a length of 40-50 mm, a fineness of 1.0 dtex, and a chitosan content of 95%; A polyurethane anti-wrinkle agent is prepared, which includes 45% of aqueous polyurethane dispersion, 4% of citric acid, 8% of sodium alginate, 10% of vegetable oil-based silicone, 2% of cellulose nanocrystals and 1% of soybean lecithin.

[0050] 6.5 kg of cotton fiber, 2.5 kg of porous polyester fiber and 1 kg of chitosan fiber were uniformly mixed using an opener and a mixer, and the mixed fibers were spun into composite yarn using a blending machine, and the yarn count of the yarn was 30s.

[0051] The spun composite yarn is plain woven on a loom with a weaving density of 120*90 yarns / 10cm.

[0052] After weaving is completed, a layer of polyurethane anti-wrinkle additive is evenly sprayed on the surface of the fabric through an atomizing spraying device, with a total spraying amount of 0.3 kg. After spraying, it is dried at 80°C and then heated to 160°C for heat setting. The processing time is 2 minutes to obtain an anti-wrinkle cotton fiber composite fabric.

[0053] Example 10 A method for preparing an anti-wrinkle cotton fiber composite fabric: The difference from Example 9 is that the total spraying amount of the polyurethane anti-wrinkle additive is 0.2 kg.

[0054] Embodiment 11 A method for preparing an anti-wrinkle cotton fiber composite fabric: The difference from Example 9 is that the total spraying amount of the polyurethane anti-wrinkle additive is 0.4 kg.

[0055] Comparative Example Comparative Example 1 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 1 is that the cotton fiber is not subjected to plasma treatment.

[0056] Comparative Example 2 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 7.

[0057] Comparative Example 3 A method for preparing a wrinkle-resistant cotton fiber composite fabric: The difference from Example 4 is that the shape memory polymer composite chitosan fiber is prepared by Preparation Example 8.

[0058] Performance testing Detection Methods Wrinkle recovery angle test Sampling: Cut a 5cm*5cm sample from the prepared wrinkle-resistant cotton fiber composite fabric.

[0059] Folding: Fold the sample along the center line under a pressure of 100N and keep the folded state for 5 minutes.

[0060] Unfolding: After releasing the pressure, unfold the fabric immediately and let the sample recover naturally for 5 minutes, and irradiate with UV light at 60℃.

[0061] Measuring angle: Use an angle measuring instrument to measure the angle between the flat state restored to by the fabric and the completely flat state, record the restored angle, repeat the above operation 5 times, and calculate the average restored angle.

[0062] When the recovery angle is close to 180°, the anti-wrinkle effect is best. The larger the recovery angle, the better the anti-wrinkle performance of the fabric.

[0063] 2. Softness test Sampling: Cut a standard size 20cm*2.5cm long sample from the fabric.

[0064] Fix the sample: Fix one end of the sample to the bender and keep the other end free.

[0065] Applied force: A standard load of 50 g is applied to the middle of the sample.

[0066] Measure the bend distance: Use a ruler to record the vertical bend distance of the free end. The shorter the distance, the softer the fabric.

[0067] 3. Air permeability test Sampling: Cut a circular fabric sample with a diameter of 10 cm.

[0068] Fix the sample: Install the sample on the test port of the air permeability tester to ensure it is airtight.

[0069] Apply air pressure: Apply 100Pa of air pressure on one side of the sample and let the air pass through the fabric.

[0070] Measuring air flow: Use the air permeability tester to read the amount of air passing through the sample per unit time, in m 3 The unit of record is / s.

[0071] If the permeability is too low, it means that the fabric is not breathable enough and you may feel stuffy when wearing it; if the permeability is too high, it may weaken the fabric's anti-wrinkle and warmth-retaining properties.

[0072] Table 1 Test data summary Restoration angle / ° Bending length / cm <![CDATA[Air permeability / m 3 / s]]> Example 1 175.6 3.03 6724 Example 2 173.8 3.22 6763 Example 3 174.4 3.34 6677 Example 4 178.6 3.59 6851 Example 5 177.5 3.47 6780 Example 6 177.6 3.70 6791 Example 7 177.3 3.55 6747 Example 8 177.8 3.61 6715 Example 9 177.2 3.93 6243 Example 10 176.4 3.89 6186 Embodiment 11 177.0 3.97 6151 Comparative Example 1 153.2 2.87 6566 Comparative Example 2 169.3 4.02 6427 Comparative Example 3 164.8 4.10 6327 Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that the surface of the cotton fiber after plasma treatment becomes rougher and more activated, which enhances the interaction with the porous polyester fiber and chitosan fiber, making the bonding between the fibers inside the fabric tighter. Under the action of external force, the displacement between the fibers is reduced, thereby enhancing the wrinkle resistance of the fabric and reducing the deformation and wrinkles of the fibers. Although plasma treatment changes the fiber surface, it has little effect on the softness and air permeability of the fiber. While improving the surface activity, it retains the softness and air permeability of the cotton fiber itself.

[0073] Combining Examples 4-8 and Comparative Examples 2-3 and Table 1, it can be seen that at the addition ratio of (7-8): (4-5), the mixing of PCL and chitosan can be effectively balanced to form a uniform fiber structure, which is helpful for wrinkle resistance and self-repair. By adding an appropriate amount of chitosan, the biocompatibility and mechanical strength of the fiber can be increased while maintaining the shape memory effect of PCL. The ratio of 7:4 to 8:5 can ensure the shape memory effect, while improving the strength and toughness of the fiber, and can achieve better air permeability.

[0074] It can be seen from Examples 1-3 and Table 1 that the cotton fiber is composed of 60-70% cotton fiber, 20-25% porous polyester fiber and 5-15% chitosan fiber. The cotton fiber is treated with plasma to make its surface more active, thereby enhancing the binding force with other fibers while retaining softness and hygroscopicity. The porous polyester fiber gives the fabric good air permeability and lightness, and enhances the anti-wrinkle effect. The chitosan fiber provides antibacterial, antistatic and hygroscopic properties, so that the fabric remains comfortable in a humid environment. The overall fabric not only has excellent moisture absorption and breathability, but also significantly improves wrinkle resistance and flexibility, making it suitable for long-term wear.

[0075] From Examples 1 and 4 and Table 1, it can be seen that by introducing photosensitized PCL, the fiber has shape memory properties, and the photosensitized PCL further enhances its responsiveness to light and ultraviolet rays, and has a certain reversibility, so that the fabric achieves better anti-wrinkle and recovery effects.

[0076] It can be seen from Example 1 and Examples 9-11 and Table 1 that, through the special formula of the polyurethane anti-wrinkle additive of the present application, the fabric maintains a high anti-wrinkle effect while taking into account wearing comfort and breathability.

[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wrinkle-resistant cotton fiber composite fabric, characterized in that: The fabric components include 60-70% cotton fiber, 20-25% porous polyester fiber and 5-15% chitosan fiber, and the cotton fiber is treated with plasma.

2. The wrinkle-resistant cotton fiber composite fabric according to claim 1, characterized in that: The specific steps of plasma treating cotton fibers are: The cotton fibers were laid flat and treated for 30-60 seconds in a high-frequency electric field with a power of 120-180 W in a 300-500 Pa nitrogen environment.

3. The wrinkle-resistant cotton fiber composite fabric according to claim 1, characterized in that: It also includes a polyurethane anti-wrinkle agent, and the amount of the polyurethane anti-wrinkle agent is 2-4% of the total mass of the fabric.

4. The wrinkle-resistant cotton fiber composite fabric according to claim 3, characterized in that: The components of the polyurethane anti-wrinkle auxiliary agent include, by weight percentage, 40-50% of aqueous polyurethane dispersion, 3-5% of citric acid, 5-10% of sodium alginate, 8-12% of vegetable oil-based silicone, 1-3% of cellulose nanocrystals and 0.5-2% of soybean lecithin.

5. The wrinkle-resistant cotton fiber composite fabric according to claim 1, characterized in that: The chitosan fiber is a shape memory polymer composite chitosan fiber.

6. The wrinkle-resistant cotton fiber composite fabric according to claim 5, characterized in that: The preparation method of the shape memory polymer composite chitosan fiber is as follows: The photosensitized PCL is dissolved in tetrahydrofuran to prepare a polymer solution with a mass fraction of 8%-15%, and chitosan is dissolved in a 3% mass concentration acetic acid solution to form a uniform solution with a mass concentration of chitosan of 10-15%; The photosensitized PCL solution and the chitosan solution were mixed in a mass ratio of (7-8):(4-5), and shape memory polymer composite chitosan fibers were prepared by electrospinning.

7. A method for preparing the wrinkle-resistant cotton fiber composite fabric according to any one of claims 1 to 6, characterized in that: The cotton fiber, porous polyester fiber and chitosan fiber are blended to obtain composite yarn, and then the composite yarn is woven to obtain wrinkle-resistant cotton fiber composite fabric.

8. The method for preparing the wrinkle-resistant cotton fiber composite fabric according to claim 7, characterized in that: The surface of the wrinkle-resistant cotton fiber composite fabric obtained by weaving is evenly sprayed with a polyurethane anti-wrinkle auxiliary agent and then dried.